Anthocyanin stability and antioxidant capacity of Clitoria ternatea incorporated jelly - Zaidan, U.H.; Kamaruzaman, N.S.; Azhari, F.; Gani, S.S.A. (Rynnye Lyan Resources, 2024)
Antioxidants from natural sources from Clitoria ternatea (butterfly blue pea flower) have recently received great attention as an increase in oxidative stress disease is concerning. One of the most useful bioactive compounds from C. ternatea extract is anthocyanin, which is generally unstable due to various factors. Therefore, the extraction process needs to be optimized with a condition that favours the stability of anthocyanin. The effect of sugar as a preservative on the anthocyanin stability and antioxidant capacity of C. ternatea has been studied on anthocyanin-rich jelly formulated in two different conditions using dried butterfly blue pea flowers. The extract (E), jelly with sugar (JWS), and jelly without sugar (JWOS) were analyzed for their anthocyanin stability and antioxidant capacity for 11 weeks at two storage temperatures (25°C and 4°C). Total anthocyanin content was determined by the pH differential method, while antioxidant capacity was determined by a common 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. After two weeks of storage, the total anthocyanin content in the extract and jelly samples decreased over time, with no major difference between the samples in temperature and the presence of sugar. However, the extract alone possessed a higher and better stability of anthocyanin content (56.27 µg/ mL to 7.19 µg/mL) after 14 days of storage at both temperatures (25°C and 4°C) compared to the processed food. It might be due to the processing effect on jelly samples during the analysis that might influence the final anthocyanin content (TAC). On the other hand, jelly incorporated with anthocyanin gives a significantly higher and more stable free radical scavenging activity than the extract, with no remarkable difference between jelly with sugar and without sugar at a different temperature. In addition, anthocyanin pigments from extract and jelly samples steadily degrade during storage at 25°C after 35 days of storage, which dramatically impacts colour quality and may also affect its nutritional properties. In conclusion, their food preparation (in extract or processed form) and storage temperature highly affected anthocyanin stability and its antioxidant capacity.